Surface Properties of LaNi5 and TiFe—Future Opportunities of Theoretical Research in Hydrides - Łodziana, Zbigniew (Frontiers in Energy Research, 2021)
Hydrogen in the solid state compounds is still considered as safe method of energy storage however, the ultimate metal hydrides or other materials for this purpose remain unknown. Such metal hydride shall have favorable thermodynamics and kinetics of hydrogen ad/desorption, it shall be resistant to contamination of H2 and do not constitute any environmental hazards. Theoretical investigations based on quantum mechanics approach have established position in modern materials research, however their application for design new alloys for reversible hydrogen storage with tailored properties is rarely present in the literature. The mainstream study deal with accurate prediction of thermodynamic properties and crystal structures of hydrides with respect to composition or external parameters. On the other hand, the effects related to kinetics of hydrogen transport or interaction between solid and pure or contaminated hydrogen are more demanding. They cannot be easily automated. We present the calculations of the equilibrium crystal shapes for LaNi5 and TiFe - two important materials that show reversible hydrogen cycling near ambient conditions. The surface properties are crucial for development of materials with better cyclability or resistant to hydrogen impurities. Indeed the adsorption energy of carbon oxides or water is stronger than hydrogen, and these molecules block the active sites for H2 dissociation. The present development of computational methods allows studies of properties of intermetallics related to their surface or novel catalytic applications.